Augmentation by resveratrol of the inhibitory effect of ethanol on platelet aggregation. (31st December 2023) - Ekawa, Kazumi; Marumo, Mikio; Wakabayashi, Ichiro
Abstract: Ethanol and resveratrol have been shown to inhibit platelet aggregation. The aim of this study was to determine whether resveratrol has an additional effect on ethanol-induced inhibition of platelet aggregation. Ca 2+ entry and subsequent aggregation of human platelets were measured by the fluorescence method and light transmittance method, respectively. Thromboxane B2 concentrations in media containing platelets were measured by using the enzyme-linked immunosorbent assay. Platelet aggregation induced by thrombin (0.025 U/ml) was significantly inhibited by preincubation of platelets with ethanol (0.5%). Preincubation with resveratrol (3.125 µM), which did not affect thrombin-induced platelet aggregation, significantly augmented the inhibitory effect of ethanol on platelet aggregation. Similar synergic effects of ethanol and resveratrol were found on aggregatory responses to collagen (2 µg/ml) and arachidonic acid (0.25 mM). On the other hand, the thrombin-induced increase in intracellular Ca 2+ concentration ([Ca 2+ ]i ) was not affected by ethanol alone, resveratrol alone or both ethanol and resveratrol together. In nominally Ca 2+ -free medium, arachidonic acid (0.75 mM) caused a potent platelet aggregation, which was not affected by the presence of ethanol alone, resveratrol alone, or both of them together. Thromboxane B2 formation induced by thrombin was significantly inhibited by ethanol (0.5%) alone and resveratrol (3.125 µM) alone, and these inhibitory effects were significantly augmented in the presence of both ethanol and resveratrol together. Resveratrol shows an additive effect on ethanol-induced inhibition of platelet aggregation. This effect by resveratrol is partly explained by its inhibitory action on thromboxane A2 production in platelets. In addition, both ethanol and resveratrol attenuate platelet aggregation through acting on the Ca 2+ -dependent intra-platelet pathway after an increase in [Ca 2+ ]i induced by thrombin.